2021
DOI: 10.1002/etc.5201
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Prediction of the Octanol–Air Partition Ratio

Abstract: The octanol-air equilibrium partition ratio, K OA , is frequently used to describe the volatility of organic chemicals, whereby n-octanol serves as a substitute for a variety of organic phases ranging from organic matter in atmospheric particles and soils, to biological tissues such as plant foliage, fat, blood and milk, and to polymeric sorbents.Because measured K OA values exist for just over 500 compounds, most of which are nonpolar halogenated aromatics, there is a need for tools that can reliably predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…As regards solvent purity, experimental organic phases are usually referred to as wet solvents since they can contain considerable amounts of water . An interesting example is 1-octanol, whose hydrated phase (“wet-octanol”) presents considerably different solvation properties such as the increase in the solubility of polar solutes (and decrease of apolar ones) due to its stronger hydrogen-bond acidity. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards solvent purity, experimental organic phases are usually referred to as wet solvents since they can contain considerable amounts of water . An interesting example is 1-octanol, whose hydrated phase (“wet-octanol”) presents considerably different solvation properties such as the increase in the solubility of polar solutes (and decrease of apolar ones) due to its stronger hydrogen-bond acidity. , …”
Section: Resultsmentioning
confidence: 99%
“…72 An interesting example is 1-octanol, whose hydrated phase ("wet-octanol") presents considerably different solvation properties such as the increase in the solubility of polar solutes (and decrease of apolar ones) due to its stronger hydrogenbond acidity. 72,73 As reported by Bannan et al, 20 the consideration of total immiscibility between water and the organic solvents will worsen the results of log P calculations. Results will be more affected as the polarity of the organic solvent increases since it will also increase the mutual miscibility with water.…”
Section: Role Of Mutual Solubility In Calculated Partitionmentioning
confidence: 94%
“…To address this limitation, property prediction techniques based on quantum chemistry and statistical thermodynamics, e.g., COSMOtherm, serve as an ideal complement because they rarely, or to a very limited extent, rely on experimentally derived data. Recent studies have demonstrated that COSMOtherm performed almost as well as QSARs/QSPRs based on training sets in predicting partition ratios and internal energies, with the exception of the internal energy change for dissolution in water. ,, Nevertheless, COSMOtherm calculations usually require a long time and intensive computational power because they rely on 3D geometry optimization of the molecular structure, which limits the use of this approach in high-throughput chemical screening.…”
Section: Sources For Retrieval Of Chemical Propertiesmentioning
confidence: 99%
“…Usually, values for 298 K are available. Factors and enthalpies for conversion to other temperatures have been published for various substances 29,122,123 …”
Section: Application Of the Submodelsmentioning
confidence: 99%
“…Factors and enthalpies for conversion to other temperatures have been published for various substances. 29,122,123 Liu et al ( 2013) 124 pointed out that the assumption of instantaneous gas/particle equilibrium can lead to large errors in the estimation of indoor SVOC concentrations. Therefore, in this work, the estimation of SVOC concentration is treated as a post-processing module, that is, first the indoor TSP is quantified and then the sorbed SVOC on the particles is estimated using Equation (3)…”
Section: Gas/particle Distribution Of Svocsmentioning
confidence: 99%